Pengaruh Jumlah Pajak Kendaraan Bermotor (PKB) dan Jumlah Bea Balik Nama Kendaraan Bermotor (BBNKB) terhadap Belanja Daerah Provinsi Bali Periode Tahun 2003–2017 - Maria Angelina Debbyang; I Ketut Darma; A. A. Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2018)
This research aims is to analyze the influence on the number of motor vehicle tax (PKB) and the number of motorbike name transfer fees (BBNKB) on regional expenditure in Bali in the period 2003-2017. The method used is multiple linear regression analysis, classic assumption test and statistical test including F test (F-test) and t test (t-test). Test Result F (f-test) with a value of sig 0,000